Encapsulation and Algicidal Properties of Fermentation Products From Vibrio brasiliensis H115 - Ouyang, Liao; Liu, Yan; Chen, Huirong; Zaynab, Madiha; Yang, Xuewei; Wang, Shilin; Li, Shuangfei (Frontiers in Marine Science, 2021)
Algicidal bacteria offer an eco-friendly and promising approach for controlling harmful algae blooms (HABs). In this study, repeated batch fermentation of immobilized algicidal bacterium Vibrio brasiliensis H115 was preformed to enhance the productivity of the algicidal compounds. The highest algicidal efficiency of the fermentation products against Akashiwo sanguinea (100%) was achieved when the fermentation time was decreased from 24 h to 14 h. The fermentation broth was then spray-dried and floating microcapsules were prepared from the dried powder. The optimum preparation conditions for floating microcapsules were: sodium alginate (SA), 3%; CaCO3: SA (mass ratio), 3:4; CaCl2, 3%; citric acid, 4%; ethylcellulose, 2%; crosslinking time, 30 min. Under the optimal conditions, the floating microcapsules displayed efficient A. sanguinea cell lysis ability and the algicidal efficiency increased from 10.62% (4 h) to 100% (24 h). These results suggest that the floating microcapsules could potentially be practically used for controlling the outbreaks of A. sanguinea.